Milling of Ti6Al4V with carbon dioxide as carrier medium for minimum quantity lubrication with different oils - Gross, Daniel; Blauhöfer, Markus; Hanenkamp, Nico (Procedia Manufacturing, 2020)
Machining of difficult-to-cut materials such as nickel-based or titanium alloys lead to high static, dynamic and thermal tool loads. A crucial role is given to the used cooling lubricant. Here, the cryogenic cooling with liquid nitrogen or carbon dioxide has been investigated in recent years as a possible alternative to conventional flood cooling. The following article deals with the further development of CO2-based cryogenic cooling combined with a minimum quantity lubrication (MQL) injected directly into the liquid CO2 phase. The focus of the investigation is the experimental selection of MQL oils for this application. For this purpose, the potential of various base oils and additivated lubricants for the CO2 assisted milling of Ti6Al4V has been investigated. The suitability assessment of the lubricants has been based on the optical measurement of wear progress along the cutting edge, recording the effective cutting forces and surface roughness. Furthermore, a mathematical compensation method is presented for the compensation of the measured value drift caused by low temperatures. The results show that the potential of cryogenic MQL is largely determined by the base oil being used. It has also been demonstrated that the use of bio-based ester oils for the present process is an alternative to mineral oil-based lubricants.<br
Keywords: CMQL; milling; Titanium; force measurment